Experimental Investigation of Characterization of Isotropic Magnetorheological Elastomers - S. R. Kumbhar; Subhasis Maji; Bimlesh Kumar (New Approaches in Engineering Research Vol. 2, 2021)
A new type of smart material is the magnetorheological elastomer (MRE). By controlling an applied magnetic field, Its dynamic mechanical performances can be controlled. MRE is usually used as stiffness - changeable spring in the semi-active vibration absorber. Low dynamic damping of MRE is required for perfect vibration control effect. This research demonstrates a novel approach for fabricating isotropic MREs under normal temperatures and pressures. A variety of MR elastomer samples were made in the absence of a magnetic field utilising Sylard’s184 silicone elastomer and un-annealed electrolytic iron power 500 mesh and 15-micron size. Their dynamic properties, such as fractional change in resonant frequency and fractional change in have been investigated. The effects of iron particles and the magnetic field that was applied were studied. This research should also serve as a useful guide for developing and preparing new MR elastomers.